(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: to evaluate the rate of healing in diabetic foot ulcers treated with a biomembrane of latex proteins from Calotropis procera (BioMem CpLP) when compared to powdered hydrocolloid. Method: randomized controlled clinical trial, registered by the Brazilian Clinical Trial Registry (REBEC), according to protocol RBR-98f3j9, carried out with eight people with diabetic foot, in a diabetic foot clinic, from March to July 2019. In the experimental group (n = 04), biomembrane was applied; in the control group (n = 04), hydrocolloid powder was used. The healing rate was assessed at 30 and 60 days after starting treatment. Results: no statistical differences were found between the healing rates of the control group and the experimental group in the temporal analysis of the initial 30 days (p = 0.726) and in the 60 days following the start of treatment (p = 0.562). Conclusion: BioMem CpLP presented healing rates similar to the conventional product, being an effective and low cost alternative for the treatment of diabetic feet.